Peluang Keberlanjutan Program Penyediaan Air Minum Berbasis Komunitas (PAMSIMAS) di Kabupaten Kendal - Nugroho, Ardhianto Adhi; Maryono, Maryono (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
Drinking Water Supply Program with Community-BasedÂ (PAMSIMAS) aims to halve the proportion of people who do not have access to drinking water and basic sanitation in Indonesia. One of the areas that became the location of the implementation of the Program Pamsimas is Kabupaten Kendal, with case study: Tanjungsari, Sidorejo, and Kalirandu Gede villages. To ensure the sustainability of the program, it is necessary to people's to understanding the implementation of the program and the factors of public concern to carry out the program. The purpose of this study was to determine the characteristics of sustainability Pamsimas in Kabupaten Kendal, in those three villages, which will be achieved by using one of the qualitative research approach, which is a case study (case study research). The qualitative analysis techniques used are for qualitative description analysis and comparative analysis. The result of this research can be concluded that those three villages are well understanding on the purpose of Pamsimas program. Each villages have valuables characteristics that can support the sustainability of the Pamsimas program. The factor of public awareness of the implementation of Pamsimas influenced by community and government relations, practical reasons as well as public awareness of the importance of protecting the environment.